2017
DOI: 10.1186/s12872-017-0673-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease and diabetes associated with long-term outcomes in patients receiving percutaneous coronary intervention

Abstract: BackgroundThe effect of diabetes mellitus (DM) and chronic kidney disease (CKD) on long-term outcomes in patients receiving percutaneous coronary intervention (PCI) is unclear.MethodsA total of 1394 patients who underwent PCI were prospectively enrolled and divided into 4 groups according to the presence or absence of DM or CKD. Baseline characteristics, risk factors, medications, and angiographic findings were compared. Determinants of long-term outcomes in patients undergoing PCI were analyzed.ResultsPatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…This result is in contrast to a previous study, which observed a significantly higher risk of developing multivessel disease in patients with both DM and CKD, as compared with patients with DM alone. [21] DM seemed to increase the risk of developing multivessel disease in patients with hypercholesterolemia, but hypercholesterolemia seemed not to increase this risk in patients with DM. Moreover, the 4 groups did not differ in terms of treated number of vessels and lesions; thus, whether with hypercholesterolemia or not, the presence of multivessel disease and high SYNTAX score in DM patients may affect long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast to a previous study, which observed a significantly higher risk of developing multivessel disease in patients with both DM and CKD, as compared with patients with DM alone. [21] DM seemed to increase the risk of developing multivessel disease in patients with hypercholesterolemia, but hypercholesterolemia seemed not to increase this risk in patients with DM. Moreover, the 4 groups did not differ in terms of treated number of vessels and lesions; thus, whether with hypercholesterolemia or not, the presence of multivessel disease and high SYNTAX score in DM patients may affect long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…From our Cox multivariate analysis, regardless of age, two important comorbidities emerge as predictors of all‐cause death: diabetes mellitus and kidney failure. Previous studies 44‐46 have quantified a minimum of twofold increase in the mortality rate in patients with these comorbidities. Intensive glycemic, lipid, and blood pressure control, in addition to prehydration with normal saline at the time of procedure, remain the only methods of proven efficacy to improve outcomes 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a recent study, DM and CKD had an additive effect on adverse long-term outcomes in patients receiving PCI. The presence of CKD seemed to predict a poorer outcome than did DM 12 .…”
Section: Introductionmentioning
confidence: 87%